Against free energy, for direct perception. (29th September 2022) - Stoffregen, Thomas A.; Heath, Robert
Abstract: We question the free energy principle (FEP) as it is used in contemporary physics. If the FEP is incorrect in physics, then it cannot ground the authors' arguments. We also question the assumption that perception requires inference. We argue that perception (including perception of social affordances) can be direct, in which case inference is not required.